Cryopreservation of Chorion Cells as Prospective Object for Biotechnology - Goncharuk, E. I. (Problems of Cryobiology and Cryomedicine, 2008)
The possibility of cryopreserved chorion cell aplication for damaged cartilage restoration and burn therapy was demonstrated in experimental investigation.